2017
DOI: 10.11118/actaun201765030791
|View full text |Cite
|
Sign up to set email alerts
|

Study on the (bio)degradation Process of Bioplastic Materials under Industrial Composting Conditions

Abstract: The objective of this study was to determine the biodegradability of bioplastic materials -sponge cloths -available on the European market. They are labeled as 100 % biodegradable but not certified as compostable. The test was carried out in real composting environment. The project duration was 12 weeks. The emphasis was put on discovering whether the sponge cloths are biodegradable or not. Based on the results, it can be concluded that sponge cloths have decomposed completely (sample C and sample D). Samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As already mentioned, the term bioplastics is used to describe plastics that can either be biobased, or biodegradable, or they can feature both properties. Specifically, bio-based plastics are actually the polymers that have their carbon partially or wholly produced from renewable resources such as proteins and lipids [6,33,[49][50][51][52], whereas biodegradable plastics are the polymers that are able to mineralize into carbon dioxide, methane, water, inorganic compounds, or biomass through the enzymatic action of specific microorganisms (bacteria, algae, and fungi) under the appropriate environmental conditions [24,30,33,39,53]. In addition, there are biodegradable plastics that are The possibility to produce bioplastics from waste is of extreme importance as replacing the production of conventional plastics with bio-based polymers would require about 0.02% of the total available Earth's arable land used for agricultural products [7].…”
Section: Classification Of Bioplasticsmentioning
confidence: 99%
See 2 more Smart Citations
“…As already mentioned, the term bioplastics is used to describe plastics that can either be biobased, or biodegradable, or they can feature both properties. Specifically, bio-based plastics are actually the polymers that have their carbon partially or wholly produced from renewable resources such as proteins and lipids [6,33,[49][50][51][52], whereas biodegradable plastics are the polymers that are able to mineralize into carbon dioxide, methane, water, inorganic compounds, or biomass through the enzymatic action of specific microorganisms (bacteria, algae, and fungi) under the appropriate environmental conditions [24,30,33,39,53]. In addition, there are biodegradable plastics that are The possibility to produce bioplastics from waste is of extreme importance as replacing the production of conventional plastics with bio-based polymers would require about 0.02% of the total available Earth's arable land used for agricultural products [7].…”
Section: Classification Of Bioplasticsmentioning
confidence: 99%
“…The vast majority of biodegradable polymers are compostable (e.g., PLA, TPS), which is one of the reasons that the composting process is one of the most preferable options when it comes to the bioplastics' disposal [3,28,43,112]. Composting is an effective means for the solid waste valorization [1,92]; it has the ability to turn a heterogeneous fraction, such as organic waste combined with biodegradable-compostable plastic waste, into a homogeneous useful material [33,38,51,154]. Moreover, the CO 2 produced does not contribute to the rise of GHGs in the atmosphere, as it is already part of the elemental cycles, and specifically the biological carbon cycle [26,33,54,73].…”
Section: Biodegradation Of Bioplastics In Compostmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Itävaara et al comparing aerobic and anaerobic biodegradation of polylactide found 10% degradation in 210 days at 37 °C under the aerobic conditions as compared to 60% degradation in 100 days at 37 °C under anaerobic conditions, and concluded that the lactic acid is more favorable for anaerobic microorganisms [23]. The biodegradation depends on factors like bioplastic chemical composition, the processing technique (aerobic/anaerobic), and the operating conditions (temperature/time) [24]. As compared to aerobic degradation of bioplastic, anaerobic degradation of different types of bioplastics has not been studied extensively [25].…”
Section: Introductionmentioning
confidence: 99%
“…Testing of bioplastics by the method of being buried in the soil shows a degradation process of 80 % by soil microorganisms (Gautam and Kaur, 2013). In other hand, biodegradation of bioplastics materials strongly depends on both, the environment where they are placed and the chemical nature of the material (Adamcová et al, 2017). The rate of degradation is also influenced by the availability of the hydrolase enzyme produced by microorganisms (Danso et al, 2019).…”
Section: Resultsmentioning
confidence: 99%